The Curious Surge of Productivity in U.S. Restaurants - Goolsbee, Austan; Syverson, Chad; Goldgof, Rebecca; Tatarka, Joe (The Review of Economics and Statistics, 2026)
Abstract After remaining flat for decades, labor productivity at U.S. restaurants surged 15% during the COVID pandemic. The surge has persisted. We explore this using mobile phone data tracking visits and spending at 100,000 limited-service restaurants. It cannot be explained by scale economies, market power, or mechanical consequences of COVID demand fluctuations. However, restaurants’ productivity growth is strongly correlated with the share of their customers visiting for 10 minutes or less, which rose considerably during COVID and persisted. This restaurant-level relationship between labor productivity and customer dwell time is large enough to explain most of the aggregate productivity increase.